PIP aquaporin pH-sensing is regulated by the length and charge of the C-terminal region - Scochera, Florencia Paola; Zerbetto de Palma, Gerardo Gabriel; Canessa Fortun, Agustina; Chevriau, Jonathan; Toriano, Roxana Mabel; Soto, Gabriela Cynthia; Zeida, Ari; Alleva, Karina (Wiley Blackwell, 2022)
Plant PIP aquaporins play a central role in controlling plant water status. The current structural model for PIP pH-gating states that the main pH sensor is located in loopD and that all the mobile cytosolic elements participate in a complex interaction network that ensures the closed structure. However, the precise participation of the last part of the C-terminal domain (CT) in PIP pH gating remains unknown. This last part has not been resolved in PIP crystal structures and is a key difference between PIP1 and PIP2 paralogues. Here, by a combined experimental and computational approach, we provide data about the role of CT in pH gating of Beta vulgaris PIP. We demonstrate that the length of CT and the positive charge located among its last residues modulate the pH at which the open/closed transition occurs. We also postulate a molecular-based mechanism for the differential pH sensing in PIP homo- or heterotetramers by performing atomistic molecular dynamics simulations (MDS) on complete models of PIP tetramers. Our findings show that the last part of CT can affect the environment of loopD pH sensors in the closed state. Results presented herein contribute to the understanding of how the characteristics of CT in PIP channels play a crucial role in determining the pH at which water transport through these channels is blocked, highlighting the relevance of the differentially conserved very last residues in PIP1 and PIP2 paralogues.
Keywords: Ciencias naturales::Ciencias biológicas::Biofísica